Modern American short story sequences composite fictions and fictive communities - Kennedy, J. Gerald 1947- (Cambridge University Press, 1995)
Originally published in 1995, this book gathers together eleven full-length essays on important American short story sequences of the twentieth century. The introduction by J. Gerald Kennedy elucidates problems of defining the genre, cites notable instances of the form (such as Sherwood Anderson's Winesburg, Ohio), and explores the implications of its modern emergence and popularity. Subsequent essays discuss illustrative works by such figures as Henry James, Jean Toomer, Ernest Hemingway, Richard Wright, William Faulkner, Eudora Welty, J. D. Salinger, John Cheever, John Updike, Louise Erdrich, and Raymond Carver. While examining distinctive thematic concerns, each essay also considers implications of form and arrangement in the construction of composite fictions that often produce the illusion of a fictive community
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1900-2000; Geschichte 1900-1990; Short stories, American / History and criticism; American fiction / 20th century / History and criticism; Community life in literature; Narration (Rhetoric); Cycles (Literature); Fiction / Technique; Literary form; Kurzgeschichte; Zyklus; USA; Aufsatzsammlung